Financial Performance Analysis at PT. Mandala Multifinance Tbk, which is listed on Indonesia Stock Exchange - Yusliana, Yusliana; AR, Mulyadi; Hanifa, Lia (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2023)
This study aims to determine the financial performance at PT. Mandala Multifinance Tbk from 2019 to 2021. The type of research used is descriptive with a quantitative approach. The data obtained is the financial statements of PT. Mandala Mutifinance Tbk, which is listed on the Indonesia Stock Exchange (BEI) from 2019 to 2021. Quantitative data is data in numerical form. In this study, qualitative data in the form of financial reporting data were obtained from PT. Mandala Multifinance, Tbk is listed on the Indonesia Stock Exchange. Data analysis techniques used to measure financial performance by using the analysis of liquidity ratios, solvency ratios and profitability ratios. The results showed that the financial performance at PT. Mandala Multifinance Tbk is based on a "very good" current ratio. while in terms of the cash ratio in a "less good" condition. based on the solvency ratio in terms of the debt to asset ratio and debt to equity ratio in "good" condition. and based on profitability ratios in terms of return on assets and return on equity in a "not good" condition.